THE EFFECT OF CAREER GROWTH ON THE TURNOVER INTENTION IN EMPLOYEES OF STARTUP X - Anna Handayani; Fendy Suhariad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Career development is a measure for a person who is developing himself in the organization where he works. It can be said that career growth is the level of perception that an individual has of the career possibilities that exist in his organization. However, it is known that career development also has an influence on turnover intentions, especially in the startup business. Aim For this reason, this research aims to determine the effect of Career Growth on turnover intention on startup X employees in Surabaya